Understanding a constellation of eight COVID-19 disease prevention behaviours using the COM-B model and the theoretical domains framework: a qualitative study using the behaviour change wheel - Chater, Angel M.; Brook-Rowland, Phoebe; Tolani, Foyeke; Christopher, Emily; Hart, Jo; Byrne-Davis, Lucie M. T.; Moffat, Abby; Shorter, Gillian W.; Epton, Tracy; Kamal, Atiya; O’Connor, Daryl B.; Whittaker, Eleanor; et al. (Frontiers in Public Health, 2023)
Background The use of behavioural science and behaviour change within local authorities and public health has supported healthful change; as evidenced by its importance and contribution to reducing harm during the COVID-19 pandemic. It can provide valuable information to enable the creation of evidence-based intervention strategies, co-created with the people they are aimed at, in an effective and efficient manner. Aim This study aimed to use the COM-B model to understand the Capability, Opportunity and Motivation of performing a constellation of eight COVID-19 disease prevention behaviours related to the slogans of ‘Hands, Face, Space, Fresh Air’; ‘Find, Isolate, Test, (FIT), and Vaccinate’ in those employed in workplaces identified as high risk for transmission of the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) to support intervention development. Methods This qualitative study recruited twenty-three participants (16 female, 7 male), who were interviewed from three environments (schools, care homes, warehouses) across three local authorities. Semi-structured interviews were analysed using thematic analysis. Findings Ten core themes were identified inductively; (1) knowledge and skills, (2) regulating the behaviour, (3) willingness to act, (4) necessity and concerns, (5) emotional impact, (6) conducive environment, (7) societal influence, (8) no longer united against COVID-19, (9) credible leadership, and (10) inconsistent adherence to COVID-19 prevention behaviours. Themes were then deductively mapped to the COM-B model of behaviour change and the theoretical domains framework and a logic model using the behaviour change wheel (BCW) was produced to inform intervention design. Conclusion This study offers a novel approach to analysis that has included eight behaviours within a single thematic analysis and COM-B diagnosis. This will enable local authorities to direct limited resources to overarching priorities. Of key importance, was the need for supportive and credible leadership, alongside developing interventions collaboratively with the target audience. COVID-19 has had an emotional toll on those interviewed, however, promoting the value of disease prevention behaviours, over and above their costs, can facilitate behaviour. Developing knowledge and skills, through education, training, marketing and modelling can further facilitate behaviour. This supports guidance produced by the British Psychological Society COVID-19 behavioural science and disease prevention taskforce.